Tingkat Efisiensi Wilayah Kabupatn dan Kota Dalam Industri Manufaktur di Jawa Barat Tahun 1987, 1992, dan 1997 - Pribadi, Krishna Nur (Center for Research and Community Services ITB, 2000)
The study is an application of Data Envelopment Analysis (DEA) method as an approach to assess technological changes and efficiency changes of regional and city industrial manufacture production. The CCR model, BCC model and efficiency scale index will be discussed to measure these changes.